Perception of Youth Towards LGBTIQ Community: A Study Among College Students in Kathmandu - Sparsha Acharya (Interdisciplinary Journal of Management and Social Sciences, 2024)
This paper focuses on the attitude of youths towards LGBTIQ community. It highlights few emergent issues on gender identities particularly the sexual and gender minorities. The major aim of this paper is to identify knowledge of youths and their attitude about the third-gender community. For this purpose, one hundred students of bachelor degree level at few selected colleges in Kathmandu Valley have been sampled for a structured questionnaire. The result shows that the perception of youths toward LGBTIQ community is becoming positive and the overall perception of society has been changing gradually from stereotyped to normalized. The crux that this paper finds with regard to the LGBTIQ community is that they have begun to be accepted as dignified human beings.